Real-time multi-marker measurement of organic compounds in human breath: towards fingerprinting breath - White, Iain R; Willis, Kerry A; Whyte, Chris; Cordell, Rebecca; Blake, Robert S; Wardlaw, Andrew J; Rao, Satish; Grigg, Jonathan; Ellis, Andrew M; Monks, Paul S (Journal of breath research, 2013)
The prospects for exploiting proton transfer reaction-time of flight-mass spectrometry (PTR-ToF-MS) in medical diagnostics are illustrated through a series of case studies. Measurements of acetone levels in the breath of 68 healthy people are presented along with a longitudinal study of a single person over a period of 1 month. The median acetone concentration across the population was 484 ppbV with a geometric standard deviation (GSD) of 1.6, whilst the average GSD during the single subject longtitudinal study was 1.5. An additional case study is presented which highlights the potential of PTR-ToF-MS in pharmacokinetic studies, based upon the analysis of online breath samples of a person following the consumption of ethanol. PTR-ToF-MS comes into its own when information across a wide mass range is required, particularly when such information must be gathered in a short time during a breathing cycle. To illustrate this property, multicomponent breath analysis in a small study of cystic fibrosis patients is detailed, which provides tentative evidence that online PTR-ToF-MS analysis of tidal breath can distinguish between active infection and non-infected patients.